The Influence of Product Quality and Completeness on Consumer Rebuying in Irian Pasar Merah Medan - Atika Aini Nasution; Aan Nurhadi (ProBisnis : Jurnal Manajemen, 2023)
Supermarket Irian is a retail company where this company provides basic daily needs such as cooking oil, food, drinks and other basic ingredients. With increasingly fierce competition in the retail sector, the Supermarket management is trying to maintain the quality and completeness of its products for the public with the aim of increasing a good impression for its consumers. The problem that occurs is how to maintain the quality and completeness of its products so that it can influence consumer repurchases and have an impact on time efficiency and a good impression for consumers who shop. Based on the description above, the research title is, "The Influence of Product Quality and Completeness on Consumer Repurchase at the Irian Pasar Merah Supermarket". The purpose of this study was to determine the effect of product quality and completeness on consumer repurchasing at Irian Pasar Merah Supermarket and the problem formulation in this study was how much influence product quality and completeness together had on consumer repurchasing at Irian Pasar Merah Supermarket . The results showed that the influence of product quality with the dimensions of performance, features, characteristics or features, reliability, conformance, service ability, aesthetics and perceived quality (impression and quality) on repurchase decisions was 20.3% . The magnitude of the influence of product completeness with the dimensions of variety (product completeness), width or breath (product availability), depth (product type and characteristics), consistency (maintaining product conformity) and balance (product adjustments) on repurchase decisions is 8.2%. That 8.6% of the repurchase decision variable (Y) is influenced by the X1 variable (product quality) and X2 variable (product completeness), while the remaining 91.4% is determined by other variables.